2008
DOI: 10.3885/meo.2008.res00261
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Knowledge Acquisition in a Cognitive Flexibility-Based Computer Learning Environment

Abstract: BackgroundA computer-based learning experience was developed using cognitive flexibility theory to overcome the pitfalls often encountered in existing medical education. An earlier study (not published) showed significant pretest-posttest increase in scores, as well as a significant positive correlation between choosing to complete the module individually or in pairs.MethodThis experience was presented as part of a second-year course in medical school with randomized assignment for students to complete the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Transfusion e‐learning that attempts to address this higher order thinking by adhering to Cognitive Flexibility Theory, was delivered to 101 second‐year undergraduates in the US. Heath et al () were able to demonstrate significant increase in application of transfusion knowledge (rather than transfusion knowledge per se ), which was maintained whether the module was undertaken alone or in pairs using collaborative learning. Regrettably feedback from the students undertaking the transfusion e‐learning was negative in 92% of cases.…”
Section: Discussionmentioning
confidence: 96%
“…Transfusion e‐learning that attempts to address this higher order thinking by adhering to Cognitive Flexibility Theory, was delivered to 101 second‐year undergraduates in the US. Heath et al () were able to demonstrate significant increase in application of transfusion knowledge (rather than transfusion knowledge per se ), which was maintained whether the module was undertaken alone or in pairs using collaborative learning. Regrettably feedback from the students undertaking the transfusion e‐learning was negative in 92% of cases.…”
Section: Discussionmentioning
confidence: 96%
“…Four content areas are covered: adverse events of blood donation and transfusion, platelets (PLTs) and TM, plasma and TM, and surgical topics in TM. These have been used in the curriculum for medical students, residents, and fellows at the University of Colorado School of Medicine and are effective as a learning intervention 26 …”
Section: Instructional Strategiesmentioning
confidence: 99%
“…The IPBL method has yielded collective feedback, which provided accurate and specific answers with some details while neglecting some crucial points. On this matter, many studies have suggested that in the presence of cognitive complexity, adequate time was necessary for gradual development of these essential managerial skills in order to empower the student and facilitate deep approaches to learning (Honebein, Duffy & Fishman, 1991;Morrison & Murray, 1994;Heath, Higgs & Ambruso, 2008;Amesse & et al, 2008). It seemed effective only for learning matters of schoolchildren with an undersized curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the online learning method is increasing in popularity. It is challenging and stimulating to the curiosity of students, as well as promptly interacting with other databases (Towle, Godolphin, Grams & Lamarre, 2006;Rossett & McDonald, 2006;Heath, Higgs & Ambruso, 2008;Cadwell, 2008;Modica & et al, 2009). Students are highly independent in studying to the selected subjects of their current interest with a complete scope of content and quality.…”
Section: Introductionmentioning
confidence: 99%